Ensuring Stable Development of the Regional Agro-Industrial Complex on the Basis of Its Clustering - DORZHIEVA, Elena Victorovna (Journal of Environmental Management and Tourism; Vol 8 No 2 (2017): JEMT Volume VIII Issue 2(18) Spring 2017DO - 10.14505//jemt.v8.2(18).08, 2017)
The article considers problems related to the long-term efficient development of the Russian agro-industrial complex in the context of anti-Russian economic sanctions. It considers theoretical aspects of stable development of the agro-food sector and perspective areas of its clustering. It is determined that the formation of agro-ecological clusters that combine small and medium-sized agro-business on the territory of the region will contribute to the increase in the level and quality of the rural population. Special strategic and social importance of the agrarian sector, disputability and insufficient sophistication of the issues related to its stable development prove the timeliness and urgency of researches in this area.